2015
DOI: 10.1021/es504808g
|View full text |Cite
|
Sign up to set email alerts
|

Transgenerational Effects of Two Antidepressants (Sertraline and Venlafaxine) on Daphnia magna Life History Traits

Abstract: The low levels of antidepressants detected in surface waters currently raise concern about their potential long-term risks to nontarget aquatic organisms. We investigated the transgenerational effects of sertraline, a selective serotonin reuptake inhibitor, and venlafaxine, a serotonin-norepinephrine reuptake inhibitor, on the life traits of Daphnia magna over two generations under environmentally realistic concentrations. We also studied the reversibility of the effect using recovery experiments. We assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(23 citation statements)
references
References 49 publications
2
17
0
4
Order By: Relevance
“…Although no differences in patterns were observed for energy reserves within generations and exposures to carbendazim, a trade‐off seemed to have occurred that can be seen by examining r and the longevity of an organism. Several authors have reported that D. magna had the ability to switch life history responses under exposure to stressors (Minguez et al ), and in the present study reproduction was found to be more favored than survival. Different patterns may be explained by the nature of a chemical, but the level of concentration used should also be considered.…”
Section: Resultssupporting
confidence: 65%
“…Although no differences in patterns were observed for energy reserves within generations and exposures to carbendazim, a trade‐off seemed to have occurred that can be seen by examining r and the longevity of an organism. Several authors have reported that D. magna had the ability to switch life history responses under exposure to stressors (Minguez et al ), and in the present study reproduction was found to be more favored than survival. Different patterns may be explained by the nature of a chemical, but the level of concentration used should also be considered.…”
Section: Resultssupporting
confidence: 65%
“…Hence, the modifications of energy allocation observed in F2 organisms (i.e., earlier puberty and reduction of egg reserves) translated in a lower growth ability of F3 offspring. Such cross generation trade-offs were previously reported in Gammarus [61], in Daphnia [62], and in the oyster Saccostrea glomerate [63], where a decrease in the amount of energy allocated to eggs due to direct exposure to contaminant led to smaller offspring. Therefore, we might describe here a cascading model of changes in the life-history traits of G. fossarum that originates from a reduction of F1 brood size, which then has resulted in an increased energy allocation to reproduction in F2 females, and then a reduced growth in F3 juveniles.…”
Section: Cascading Effects On F1 F2 Reproductive Features and F3 Grosupporting
confidence: 70%
“…The relatively high concentration (∼50 μg L −1 ) of venlafaxine caused significant effects in the F 0 and 18S rRNA gene expression, indicating that algae could be the most concerned (without discarding protozoa or fungi). This chemical has an up to now unknown mode of action on algae, though it acts as a serotonin–norepinephrine reuptake inhibitor and affects the reproduction and metabolism of cladocerans and fish ( Henry et al, 2004 ; Galus et al, 2013 ; Minguez et al, 2015 ). On the other hand, diuron inhibits algal photosynthesis by blocking the electron transfer at PSII ( Kumar et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%